(untitled) (Journal of the College of Education for Women, 2023)
The human being is a social being and human communication is a fundamental axis in the process of social interaction, and the characteristic of social shyness grows through the interaction of the individual with his environment. Identifying the level of shyness among university students, and identifying the differences in shyness among university students according to specialization (scientific, humanities). In order to achieve the objectives of the research, the researcher prepared a measure of shyness based on Zimbardo’s theory, and the components that he identified are the (behavioral, cognitive, and emotional components). The validity and reliability were calculated using the Cronbach’s alpha method, reaching (0.94), and the scale in its final form consisted of (38) items valid for measuring shyness. The researcher applied the scale to a research sample of (160) female students from two majors (scientific, humanities). The researcher reached some conclusions, the most important of which are: The individuals in the research sample do not have high shyness, and there is no statistically significant difference in shyness between female students in scientific and humanities colleges.